Advertising - Creager, Sid Henry (My University, 1895)
Introduction: Go forth in haste with bills and paste; proclaim to all creation that men are wise, who advertise, for this our generation. For the world of business, if there is one thing more potent than another to prosper and to win men, it is advertising. The almighty dollar may move the earth, but advertising moves the dollar. We cannot escape it if we would. If we shun it ourselves we will only fall victims to other men’s advertising. A thing so powerful which we cannot escape, we may well study that we may know how to manipulate it in our favor.
Citation: Creager, Sid Henry. Advertising. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Business; Advertising; Power of advertising; Manipulation; Theses; Manuscripts (documents)